The underlying dimensions of relationship marketing in the Malaysian mobile service sector - Bojei, Jamil; Abu, Mimi Liana (Routledge, 2014)
After so many years, the Malaysian mobile service market is getting saturated, whereby service operators are having difficulties differentiating themselves because they offer similar services. As the service options are wide, customers become less committed to a particular provider and might easily shift from one operator to another. This situation forces the service providers to create a strategy that focuses more on gaining and retaining long-term relationships with their customers. Therefore, the objective of this study is to determine the underlying dimensions of relationship marketing in the Malaysian mobile service sector. A sample of 300 customers in Klang Valley was drawn using scientific procedures of mall intercept, and structural equation modeling was utilized in testing the proposed model. The results show that the relationships between the exogenous latent factors and the overall endogenous factor are significant, ranging from.77 to.94. This illustrates that a relatively high proportion of the variance in relationship marketing is well explained by each of the factors.